Increasing PAI Learning Results with Index Cart Mach (IKM) Learning Methods Students Class IV (Four) SDN 17 Sentosa Padang Gelugur Kecamatan Padang Gelugur - Khoirun Saleh (BiCED Proceeding, 2024)
This study aims to determine the impact of implementing the Index Card Match method in Islamic Religious Education learning in grade IV. The research was conducted in two cycles, with the first cycle showing suboptimal results, as only 55% of students reached the Minimum Mastery Criteria (KKM). In the second cycle, improvements were made by providing more detailed explanations and better classroom management, resulting in 75% of students achieving KKM. In addition, student activity increased, as seen from active participation in discussions and interactions during the learning process. The findings of this study show that the application of the Index Card Match method can improve student learning outcomes, both in terms of KKM achievement and a more conducive classroom environment.